Al-Qur'an dan Keadilan Islam dalam Pensyariatan Hudud - Muhammad Syahrial Razali Ibrahim (Sharia and Law Faculty, 2012)
This paper represents an attempt to restore the Muslims view toward the right understanding of Islam and its teachings, particularly in matter of law enforcement in penalty law (hudud). In fact, Islam is not a religion that only focuses on sanctions and penalties, but instead, mercy is the essence of Islamic teachings. Shari’a was revealed for the benefit of human beings. Therefore, before the sanction imposed, Islam had already set the Muslims to avoid all those sanctions.